Globalization on the decline: the G20 must take a new stance against protectionism - Gnath, Katharina; Petersen, Thiess (Gütersloh, 2016)
"The globalization engine has faltered in recent years. The bursting of the dotcom bubble in March 2000 caused globalization, which is understood to mean economic, political and social interconnection between countries, to stagnate in the most important industrialized nations. In the majority of industrialized countries, the bankruptcy of Lehman Brothers in September 2008 even led to a decrease in global interconnectedness."